2017
DOI: 10.4317/jced.53110
|View full text |Cite
|
Sign up to set email alerts
|

Resin infiltrant for non-cavitated caries lesions: evaluation of color stability

Abstract: BackgroundThe objective of this in vitro study was to evaluate the over time color stability of one resin infiltrant (Icon) upon exposure to staining solutions (coffee and wine) compared with one nano-hybrid sealant (Grandio Seal), one transparent fissure sealant with fluoride (Control Seal) and one nanofilled composite (Filtek Supreme XTE).Material and MethodsAll materials were polymerized according to manufacturers’ instructions into silicon rings (height 1 mm; internal diameter 6 mm; external diameter 8 mm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 25 publications
4
25
0
9
Order By: Relevance
“…This means that storage in water caused a color change in resin-based materials that can be considered clinically significant and noticeable, whilst storage in grape juice induced color alterations for all experimental groups. These results are in agreement with other studies which demonstrated significant changes in color after coloring processes related to storage in pigmented solutions 6,26,29,31 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This means that storage in water caused a color change in resin-based materials that can be considered clinically significant and noticeable, whilst storage in grape juice induced color alterations for all experimental groups. These results are in agreement with other studies which demonstrated significant changes in color after coloring processes related to storage in pigmented solutions 6,26,29,31 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that such parameters are enough to evaluate white spot lesions, since these lesions are more opaque and whiter than healthy enamel. Although some studies use CIEDE2000 system (ΔE 00 ) to assess color measurements, the CIE-Lab system is still a reliable system used and has been used in recent studies to evaluate color stability of white spot lesions 7,26 .Based on this CIE-Lab system, it is possible to calculate the ΔE ab and compare it with a visual perception already reported in the literature (color variation is imperceptible when <1, clinically acceptable when ≤3.3 and unacceptable when above 3.3) 22 . In the present study, color coordinates were obtained at several time intervals as described in the materials and methods section.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the results of this study, we can observe that the most affected parameter was L*, indicating low brightness of the samples subjected to exogenous colorants. We have also found in accordance with the results obtained in other studies, that the polishing of materials allows an improvement in color parameters [20, 39,49].…”
Section: Experimental Partsupporting
confidence: 92%
“…However, the results of various studies on color changes induced by exogenous colorants on dental surfaces with incipient caries and on the materials used in their treatment are often controversial [31][32][33][34][35]. Researchers have proposed several methods to evaluate the color changes parameters: colorimetry, guides, color keys, devices, clinical comparison or spectrophotometry [20, [36][37][38][39][40]. The spectrophotometer allows the evaluation of the L*, a* and b* parameters, meaning the color of the specimens in all axes.…”
Section: Experimental Partmentioning
confidence: 99%
“…Materials were polymerized into silicon rings (external diameter 9 mm, internal diameter 6 mm, thick 2 mm) to obtain identical specimens. [ 27 ] Cavities of these rings were slightly overfilled with material, covered with Mylar Matrix Strip (Henry Schein, Melville, NY, USA), pressed between two glass plates and polymerized for 40 s on each side using a curing unit (Celalux II, Voco, Cuxhaven, Germany). One light polymerization mode was used for each material standard: 1000 mW/cm 2 for 40 s. The light was placed perpendicular to the specimen surface, at distance of 1.5 mm or less.…”
Section: Methodsmentioning
confidence: 99%